2016
DOI: 10.1515/aiht-2016-67-2753
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C pretreatment protects from nickel-induced acute nephrotoxicity in mice

Abstract: Nickel is an abundant carcinogenic and nephrotoxic metal whose activity leads to renal impairment. Previous studies have shown a protective effect of simultaneous vitamin C administration on acute and chronic nickel toxicity. However, very little research relating to the effect of vitamin C pretreatment in preventing nickel-induced acute nephrotoxicity is available. Therefore, the present study aimed to determine the efficiency of vitamin C (VC) pretreatment in preventing acute renal toxicity of nickel. Mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Vitamin C also protects against NSAID-induced AKI in rats by improving kidney function and renal lesions, serum oxidative stress, and tissue inflammation, comparatively to vitamin E administration [ 89 ]. It is also protective against nickel-induced toxicity in mice, by improving renal function, inflammation and renal tubular degeneration, and necrosis [ 128 ]. This finding supports earlier evidence of decreased nickel-induced oxidative stress in other organ systems with ascorbate [ 129 ].…”
Section: Vitamin C and Renal Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C also protects against NSAID-induced AKI in rats by improving kidney function and renal lesions, serum oxidative stress, and tissue inflammation, comparatively to vitamin E administration [ 89 ]. It is also protective against nickel-induced toxicity in mice, by improving renal function, inflammation and renal tubular degeneration, and necrosis [ 128 ]. This finding supports earlier evidence of decreased nickel-induced oxidative stress in other organ systems with ascorbate [ 129 ].…”
Section: Vitamin C and Renal Protectionmentioning
confidence: 99%
“…This finding supports earlier evidence of decreased nickel-induced oxidative stress in other organ systems with ascorbate [ 129 ]. Interestingly, vitamin C supplementation reduces nickel accumulation in the kidney [ 128 ], suggesting benefit independent of ROS scavenging.…”
Section: Vitamin C and Renal Protectionmentioning
confidence: 99%
“…Therefore, the elevation of both products in the group treated with NiCl 2 could be due to the nephrotoxic effect of NiCl 2 to renal cells. Earlier works have shown that NiCl 2 is a nephrotoxin and similar elevation of creatinine and urea were observed in mice [53]. Renal impairment often results in perturbation of electrolytes balance.…”
Section: Discussionmentioning
confidence: 55%
“…[12][13][14][15][16] In some previous studies, oral administration of vitamin C showed remarkable protection against kidney damage and histopathological changes induced by cisplatin, lead, and nickel in rats. [33][34][35] More investigations are needed to explain the underlying mechanisms of the protective effects that remain unexplained. The small sample size and limited CME dose range are limitations of the current study.…”
Section: Discussionmentioning
confidence: 99%